A cognitive-pragmatic análisis in British and AmericanNews - Roldán Castro, Josefa (Epos : Revista de filología, 2011)
The aim of this study is to analyze two articles in two different newspapers (The Guardian and Herald Tribune) to underline, following a rhetorical exposition, not only the parallels between them in terms of the information given and the incidents mentioned, but also the striking differences or contrasts in their treatment of the same event. This comparative analysis will follow two of the three main rhetorical components, that is: invention and disposition . In «invention» we shall deal with the semantic contents or subject matter of the news: deployment of missiles versus disarmament proposals. The main function of language displayed is the communicative one, and as it highlights the content of the message, the language is making use of the referential or denotative function in contrast to the connotative function . Arrangement or «disposition » contains an analysis of the structural scheme of both news texts, that is, how the previous material is organized into structural form. In this structural part we shall analyze the main parts of a news item: its headline, lead and the body. The news item adopts the structure of an inverted triangle: the most important facts appear in the » headline » and are explained in the » lead ». Although the two headlines treat the same event, they usually adopt different point of views in their treatment in the headline and the place they occupy within the paper. Emphasis will be laid on one of the three major functional-semantic components of a text: the ideational element, the field which tends to determine the transitivity pattern, types of processes, participants and settings (or circumstances). We are going to apply to these journalistic texts mainly a cognitive approach, but also a functional one, analyzing the processes and their components to deduce which ones are the commonest and why. To conclude, the contrast in newspaper styles is best seen when different newspapers deal with the same story right from the opening lines of a news item. These two articles are clear examples of journalistic language, in which the semantic contents are more or less the same although each newspaper focuses them according to a different point of view, paying attention to the elements which could more strongly interest their respective readers. This is related somehow to three main » cognitive linguistic » perspectives: experiential view, the prominence view, and attentional view. Finally, this comparative analysis will allow us to see how the culture and the ideology of the newspaper can influence the treatment of the same event. El objetivo de este estudio es analizar dos artículos periodísticos en dos periódicos diferentes (The Guardian y Herald Tribune) para resaltar, siguiendo una exposición retórica, no solamente las similitudes entre ellos en cuanto a la información publicada y los incidentes mencionados, sino también las diferencias más llamativas a la hora de tratar el mismo hecho. Este análisis comparativo tendrá como base dos de los tres principales componentes de la Retórica, es decir: «inventio» y «dispositio». En «inventio» nos centraremos en los contenidos semánticos o tema principal de la noticia: el despliegue de misiles frente a las propuestas de desarme. La principal función del lenguaje utilizada es la comunicativa y, al poner énfasis en el contenido del mensaje, se está haciendo uso de la función referencial o denotativa frente a la connotativa. «Dispositio» consiste en un análisis estructural de ambos textos, estos es, cómo el material anterior se organiza de manera estructurada. En este apartado dedicado a la estructura, analizaremos los principales componentes de una noticia: titular, encabezamiento y desarrollo o cuerpo. Las noticias periodísticas adoptan la forma de un triángulo invertido, ya que los hechos más importantes aparecen en el titular y se desarrollan en el encabezamiento. Aunque los dos titulares tratan el mismo tema, suelen adoptar diferentes puntos de vista al resumirlo en sus respectivos titulares, ocupando éstos distintos lugares en el periódico. Se hará hincapié en uno de los tres principales componentes funcionales-semánticos del texto: el elemento ideacional, el campo que determina el modelo de transitividad, tipos de procesos, participantes y circunstancias. Se aplicará a estos textos periodísticos una metodología cognitiva funcional a la hora de analizar los procesos y sus componentes para concluir cuáles son los más comunes y por qué. Como conclusión, el contraste en los estilos periodísticos se percibe mejor cuando diferentes periódicos tratan la misma noticia desde sus primeras líneas. Estos dos artículos son un claro ejemplo de lenguaje periodístico, en los que los contenidos semánticos son más o menos los mismos, aunque cada periódico los interpreta según su punto de vista, prestando más atención a los hechos que podrían interesar más a sus lectores respectivos. Esto está de alguna manera relacionado con los tres principales enfoques de la lingüística cognitiva: «punto de vista de la experiencia, de la importancia y de la atención.»Finalmente, este análisis comparativo nos permitirá demostrar cómo la cultura y la ideología de un periódico puede influir en el tratamiento de un mismo hecho.